Single-Dose Bioequivalence Study of Rivaroxaban-Containing Medicinal Products in Healthy Volunteers - G. N. Gildeeva; A. A. Chaplenko; V. I. Yurkov; E. S. Stepanova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2022)
Therapeutically, new oral anticoagulants (NOACs) are considered to be non-inferior or superior to vitamin K antagonists (warfarin). NOACs are included in current guidelines for the treatment of various cardiovascular diseases. Rivaroxaban medicinal products have been shown to effectively fight thrombotic complications of the new coronavirus infection, COVID-19. The wide clinical use of rivaroxaban products motivates the development of generics.The aim of the study was to compare the pharmacokinetics and safety of rivaroxaban medicinal products in a single-dose bioequivalence study in healthy volunteers under fasting conditions.Materials and methods: the bioequivalence study compared single-dose oral administration of Rivaroxaban, 10 mg film-coated tablets (NovaMedica Innotech LLC, Russia), and the reference product Xarelto®, 10 mg filmcoated tablets (Bayer AG, Germany), in healthy volunteers under fasting conditions. The open, randomised, crossover trial included 46 healthy volunteers. Each of the medicinal products (the test product and the reference product) was administered once; blood samples were collected during the 48 h after the administration. The washout between the study periods lasted 7 days. Rivaroxaban was quantified in plasma samples of the volunteers by high performance liquid chromatography coupled with tandem mass spectrometry (HPLC-MS/MS).Results: no adverse events or serious adverse events were reported for the test and reference products during the study. The following pharmacokinetic parameters were obtained for Rivaroxaban and Xarelto®, respectively: Cmax of 134.6 ± 58.0 ng/mL and 139.9 ± 49.3 ng/mL, AUC0-48 of 949.7 ± 354.5 ng×h/mL and 967.6 ± 319.9 ng×h/mL, AUC 0-∞ of 986.9 ± 379.7 ng×h/mL and 1003.6 ± 320.4 ng×h/mL, T1/2 of 8.2 ± 3.2 h and 7.8 ± 3.3 h. The 90% confidence intervals for the ratios of Cmax, AUC0-48, and AUC0-∞ geometric means were 88.04-108.67%, 89.42-104.92% and 89.44-104.81%, respectively.Conclusions: the test product Rivaroxaban and the reference product Xarelto® were found to have similar rivaroxaban pharmacokinetics and safety profiles. The study demonstrated bioequivalence of the medicinal products.